The new international economic order - Komlev, Lev. (New Delhi, 1981)
The seventies, very recent history, have added a new term to the inter national political and economic vocabulary. This is the "New Inter national Economic Order". The term is already in wide use in UN documents and in newspapers and journals as also at regional and international symposia. This not only reflects the strong desire of the developing nations to free them selves of unequal economic an relationship with the developed West but also the general awareness in the democratic sections of public opinion in the world of the fact that a restruc turing of international relations on a more just and equitable basis must inevitably take place. Everything that has been said or done at inter national forums, including the UN, points to the obvious progressive evolution of the entire system of international relations towards this end. Equally obvious also is the fact that this does not leave everybody happy and satisfied. The Western mo nopolies, including the giant transna tional corporations, are doing their utmost to defy the natural evolution of international socio-economic relations. Their systematic opposi tion may slow down the pace but cannot thwart a movement, realiza tion of a concept, that is gaining in strength everyday. The forces pro moting the process represent a broad anti-imperialist front embracing Asian, African, Latin American countries with varying levels of economic development and social awareness but with common goals and objectives.
Keywords: International economic relations